2011
DOI: 10.1158/1940-6207.capr-11-0076
|View full text |Cite
|
Sign up to set email alerts
|

Test Performance of Immunologic Fecal Occult Blood Testing and Sigmoidoscopy Compared with Primary Colonoscopy Screening for Colorectal Advanced Adenomas

Abstract: Given the current increase in colorectal cancer screening, information on performance of screening tests is needed, especially in groups with a presumed lower test performance. We compared test performance of immunologic fecal occult blood testing (FIT) and pseudosigmoidoscopy with colonoscopy for detection of advanced adenomas in an average risk screening population. In addition, we explored the influence of gender, age, and location on test performance. FIT was collected prior to colonoscopy with a 50 ng/mL … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
34
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 40 publications
3
34
1
Order By: Relevance
“…Moreover, at any cut-off f-Hb, the sensitivity and positive predictive value for significant neoplasia (cancer plus high-risk adenoma) is substantially higher and specificity and negative predictive value lower among men than women 9. More recently, it has been demonstrated that mean f-Hb in FIT-positive individuals is significantly lower in women compared with men and for younger compared with older participants 10. Few studies11–13 have demonstrated that f-Hb increases as disease becomes more serious, from the normal through low- and high-risk adenomatous polyps (LRA, defined as <3 or any <10 mm, HRA, defined as ≥3 or any ≥10 mm) to invasive cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, at any cut-off f-Hb, the sensitivity and positive predictive value for significant neoplasia (cancer plus high-risk adenoma) is substantially higher and specificity and negative predictive value lower among men than women 9. More recently, it has been demonstrated that mean f-Hb in FIT-positive individuals is significantly lower in women compared with men and for younger compared with older participants 10. Few studies11–13 have demonstrated that f-Hb increases as disease becomes more serious, from the normal through low- and high-risk adenomatous polyps (LRA, defined as <3 or any <10 mm, HRA, defined as ≥3 or any ≥10 mm) to invasive cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Fecal-based analyses such as occult blood, immunochemical and stool DNA tests are common noninvasive screening tests [9]. Nevertheless, they are confined by low sensitivity and specificity against detection of premalignant lesions [10,11]. Although stool DNA test utilizes molecular markers such as KRAS , APC and TP53 genes as detection targets, it is not favorably recommended by the US Preventive Service Task Force due to high cost, uncertainty of test performance and labor-intensive handling [12-14].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have addressed site specific sensitivity of FITs, and most of them found somewhat lower sensitivity for proximal compared to distal neoplasms . Typically, however, no further distinction according to subsite within the proximal colon or distal colon and rectum was made.…”
mentioning
confidence: 99%